The SycN/YscB chaperone-binding domain of YopN is required for the calcium-dependent regulation of Yop secretion by Yersinia pestis - Plano, Gregory V.; Joseph, Sabrina S. (Frontiers in Cellular and Infection Microbiology, 2013)
Numerous Gram-negative bacterial pathogens employ type III secretion systems (T3SSs) to inject effector proteins into eukaryotic cells. The activation of the T3S process is tightly controlled in all T3SSs. In Yersinia pestis, the secretion of effector proteins, termed Yersinia outer proteins (Yops), is regulated by the activity of the YopN/SycN/YscB/TyeA complex. YopN is a secreted protein that interacts with the SycN/YscB chaperone via an N-terminal chaperone-binding domain (CBD) and with TyeA via a C-terminal TyeA-binding domain (TBD). Efficient YopN secretion is dependent upon its N-terminal secretion signal (SS), CBD and the SycN/YscB chaperone. In this study, we investigate the role of the YopN CBD in the regulation of Yop secretion. Analysis of YopE/YopN hybrid proteins in which the YopN SS or SS and CBD were replaced with the analogous regions of YopE indicated that the YopN CBD or SycN/YscB chaperone play a role in the regulation of Yop secretion that is independent of their established roles in YopN secretion. To further analyze the role of the YopN CBD in the regulation of Yop secretion a series of tetra-alanine substitution mutants were generated throughout the YopN CBD. A number of these mutants exhibited a defect in the regulation of Yop secretion but showed no defect in YopN secretion or in the interaction of YopN with the SycN/YscB chaperone. Finally, conditions were established that enabled YopN and TyeA to regulate Yop secretion in the absence of the SycN/YscB chaperone. Importantly, a number of the YopN CBD mutants maintained their defect in the regulation of Yop secretion even under the established SycN/YscB chaperone-independent conditions. These studies establish a role for the CBD region of YopN in the regulation of Yop secretion that is independent from its role in YopN secretion or in the binding of the SycN/YscB chaperone.